1991
DOI: 10.1093/oxfordjournals.eurheartj.a059863
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for operative mortality and morbidity in patients undergoing coronary artery bypass surgery for stable angina pectoris

Abstract: Risk factors for a poor early outcome of surgery for stable angina pectoris were evaluated in 2659 consecutive patients from a defined population. The total operative mortality (death within 30 days after surgery) was 2.6% and the frequency of myocardial injury (increase in S-ASAT to greater than 2.0 mu kat l-1 and in S-CKMB to greater than 1.5 mu kat l-1 within 48 h postoperatively or death in the operating room) 14%. Mortality was related to New York Heart Association (NYHA) classification (P less than 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…6,7,9,13,14 Revascularization procedures, ie, coronary artery bypass grafting (CABG) and percutaneous transluminal coronary angioplasty (PTCA), are standard treatments in severe angina pectoris. There are several groups of patients for whom CABG is known to be associated with an increased complication risk, eg, patients with unsuitable coronary anatomy requiring extended surgical procedures 15 ; patients with low ejection fractions 16 ; patients with concomitant extracardiac disease such as diabetes mellitus, 17 renal dysfunction, 18 cerebrovascular disease, 18 -20 or peripheral vascular disease 21 ; and patients who have previously undergone CABG. 15,17 Until now, SCS has been used in the treatment of severe angina pectoris despite optimum medication in patients who are not accessible for revascularization.…”
mentioning
confidence: 99%
“…6,7,9,13,14 Revascularization procedures, ie, coronary artery bypass grafting (CABG) and percutaneous transluminal coronary angioplasty (PTCA), are standard treatments in severe angina pectoris. There are several groups of patients for whom CABG is known to be associated with an increased complication risk, eg, patients with unsuitable coronary anatomy requiring extended surgical procedures 15 ; patients with low ejection fractions 16 ; patients with concomitant extracardiac disease such as diabetes mellitus, 17 renal dysfunction, 18 cerebrovascular disease, 18 -20 or peripheral vascular disease 21 ; and patients who have previously undergone CABG. 15,17 Until now, SCS has been used in the treatment of severe angina pectoris despite optimum medication in patients who are not accessible for revascularization.…”
mentioning
confidence: 99%
“…Acute myocardial infarction in the postoperative myocardial revascularization period is a complication that results in worse evolvement in a short-and long-term [14][15][16][17][18] . Several studies have reported measures that aim at decreasing the incidence of acute myocardial infarction in the postoperative period, in particular enhancement of myocardial protection techniques, enhancement of surgical technique (for example, use of arterial grafts, of circulatory support (especially intraaortic balloon), and pharmacological advances 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Other correlates of increased risk include increasing age; recent MI (less than 30 days), especially in the presence of unstable angina, left main disease, or 3-vessel disease; emergency or urgent coronary bypass; reoperation; reduced renal function; cerebrovascular disease; COPD; a smoking history; obesity; and female sex (21,(445)(446)(447)(448)(449)(450)(451)(452). A higher operative mortality occurs for all identified risk factors in patients aged 75 years or older than for those less than 65 years old.…”
Section: Cabg In the Elderly: Age 70 And Oldermentioning
confidence: 99%
“…Operative factors that have been reported to adversely influence hospital mortality in the elderly include the use of bilateral IMA grafts, prolonged pump time and/or crossclamp time, an increased number of grafts required, right IMA grafting, and any postoperative complication (448,449,457,458). Obesity has been identified as a risk factor for infection in patients receiving bilateral IMA grafts (457).…”
Section: Cabg In the Elderly: Age 70 And Oldermentioning
confidence: 99%